Iman dan Pertobatan: Konten Pendampingan Pastoral bagi Jemaat Menjelang Kematian Akibat Penyakit Kronis - Dwi Arya Nanda Sianturi; Ananda Dharmawan Kustiadewa; Firman Panjaitan (Sekolah Tinggi Teologi Ekumene Jakarta., 2022)
Pastoral care is urgently needed, especially for someone with a chronic illness. Through this pastoral care, people with chronic illnesses will be prepared to face death, both physically and spiritually. But more importantly than that, pastoral care to people with chronic illnesses will provide assurance that salvation from Jesus will be given to sufferers if they are willing to confess their sins and repent. Through a qualitative-descriptive method to obtain factual data conceptually, this study found that pastoral care to people who are experiencing chronic pain must be carried out by inviting sufferers to first confess all the sins they have committed as a result of their inability to love themselves. After that they must enter into repentance, so that they may obtain perfect salvation in Jesus. Thus they will return holy and ready to face chronic illness, even death.